PENGARUH PENDIDIKAN DAN PELATIHAN, MOTIVASI, SERTA LINGKUNGAN KERJA TERHADAP KINERJA GURU SMK NEGERIBANYUASIN - Handayani, Dwi (Jurnal Ilmu Manajemen, 2017)
The purpose of this study is to know and analyze the influence of educationand training, motivation, and work environment on the performance ofteachers SMK Negeri Banyuasin The study was conducted using associativedesign. In the study used four varables namely education and training,motivation, work environment, and performance that each developed intoseveral indicators. Primary data were obtained from 145 samples selectedby cluster sampling. Data collection methods used are questionnaires. Theanalysis technique used is multiple linear regression. The result of theresearch proves that 1) Education and training, motivation, and workenvironment together have significant effect on teacher performance 2)Education and training and motivation have a significant effect partially onteacher performance, while work environment gives insignificant influence toteacher performance.